Selectivity underlies the dissociation between seasonal prey availability and prey consumption in a generalist predator. Issue 7 (6th April 2018) - Whitney, Thomas D.; Sitvarin, Michael I.; Roualdes, Edward A.; Bonner, Simon J.; Harwood, James D.
Abstract: Generalist predators are capable of selective foraging, but are predicted to feed in close proportion to prey availability to maximize energetic intake especially when overall prey availability is low. By extension, they are also expected to feed in a more frequency‐dependent manner during winter compared to the more favourable foraging conditions during spring, summer and fall seasons. For 18 months, we observed the foraging patterns of forest‐dwelling wolf spiders from the genus Schizocosa (Araneae: Lycosidae) using PCR‐based gut‐content analysis and simultaneously monitored the activity densities of two common prey: springtails (Collembola) and flies (Diptera). Rates of prey detection within spider guts relative to rates of prey collected in traps were estimated using Roualdes' cst model and compared using various linear contrasts to make inferences pertaining to seasonal prey selectivity. Results indicated spiders foraged selectively over the course of the study, contrary to predictions derived from optimal foraging theory. Even during winter, with overall low prey densities, the relative rates of predation compared to available prey differed significantly over time and by prey group. Moreover, these spiders appeared to diversify their diets; the least abundant prey group was consistently overrepresented in the diet within a given season. We suggest that foraging in generalist predators is not necessarily restricted to frequency dependency during winter. In fact, foraging motives other than energy maximization, such as a more nutrient‐focused strategy, may also be optimal for generalist predators during prey‐scarce winters.